(untitled) (Conferencea, 2023)
The use of outdoor games in physical education classes at the university allows students to become involved in a healthy lifestyle, stimulate motivation to play sports, cultivate important psychophysical and personal qualities, increase the effectiveness of the physical education process at the university.